PERENCANAAN PENGENDALIAN KUALITAS BATU BATA DENGAN MENGGUNAKAN METODE SIX SIGMA PADA UD. X - Mukhlizar, Mukhlizar; Muzakir, Muzakir (Jurnal Optimalisasi, 2016)
The quality of goods or services is one of the factors that influence the consumer's attention. Improvements to the quality of the production process is done continuously to minimize product defects, one method that can be used to control the quality and overcome the number of defective products is with the Six Sigma method. From the calculations, the defective products caused by 3 decay, which amounted to 9520 due to a broken, 7598 defects due to underdonebricks and about 6,740 defects due scorched. Percentage of bricks defective to total of production is about 36%. This percentage is huge, given the controls used is 1%. From the causals diagram, there are factors that affect the defective products which are human, the burning process and materials. By using six sigma obtained DPMO value of 124,888.23 and the number six sigma of 2.69.Keywords: Six sigma, quality, defective products.